The Establishment of Poskestren (Islamic Boarding School Health Center) at Kampung At-Tauhid Islamic Boarding School, Ogan Ilir Regency - Haerawati Idris; Anggun Budiastuti; Rahmatillah Razak; Nurmalia Ermi; Desri Maulina Sari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Health issues are important in the world of education, including in Islamic boarding schools. To support the health status of santri (students at the Islamic boarding school), Islamic boarding schools need to facilitate them through Pos kesehatan pesantren or Poskestren (Islamic Boarding School Health Center). This community service aimed to establish a Poskestren at an Islamic boarding school. The methods adopted in this community service included advocacy, education, socialization, promotion, and empowerment for santri. This study used action research design. There is collaborative between researcher and student in Islamic boarding school. We collected data by survey, taking action and evaluating action. Data analysed used descriptive. The result of this community service showed the establishment of a Poskestren was supported by all parties, and a special room was provided for this health service with the necessary facilities and infrastructure at Kampung At-Tauhid Islamic Boarding School. In addition, this community service also established Kader Santri Husada (Santri Husada Cadres) consisting of nine santri whom the campus and community health center had trained regarding emergencies, use of medical devices, personal hygiene, and prevention of sexually deviant behavior. It is expected that the Poskestren can provide services for all communities at the Islamic boarding school on an ongoing basis. It is also expected that the Islamic boarding school and community health center can continue the development of this Poskestren service.